Exopolysaccharide-producing strains alter heavy metal fates and bacterial communities in soil aggregates to reduce metal uptake by pakchoi - Zhang, Heyun; Zhang, Junqing; Tang, Shuangjiao; Deng, ZhongYan; Makar, Randa S.; Yao, Lunguang; Han, Hui (Frontiers in Microbiology, 2025)
The characteristics of heavy metals in soil aggregates represent critical factors influencing the uptake of heavy metals by crops. However, the mechanisms underlying the immobilization of Cd and Pb by soil aggregates of different particle sizes mediated by exopolysaccharide (EPS)-producing bacteria have remained poorly understood. In this study, a selective medium was employed to isolate and screen EPS-producing bacteria from the heavy metal-contaminated soil, with their mechanisms of Cd and Pb immobilization investigated through solution adsorption experiments. Pot experiments combined with high-throughput sequencing technology were conducted to examine the effects of these strains on heavy metal uptake by pakchoi and to elucidate the underlying microbiological mechanisms. Two high-EPS-yielding bacterial strains, Pseudomonas sp. H7 and Agrobacterium sp. Z22, were successfully isolated from heavy metal-contaminated farmland. These strains effectively facilitated the formation of Fe2Pb(PO4)2, CdCO3, and Pb2O3 precipitates, thereby immobilizing Cd and Pb in aqueous solutions. Compared to the CK group, inoculation with Pseudomonas sp. H7 and Agrobacterium sp. Z22 reduced the Cd (30.7–81.8%) and Pb (8.1–57%) contents in the pakchoi tissues. Notably, Pseudomonas sp. H7 and Agrobacterium sp. Z22 enhanced EPS production and promoted the specific formation of CdCO3, PbCO3, Cd2(OH)2CO3, and 2PbCO3·Pb(OH)2 within microaggregates (< 250 μm), which significantly reducing Cd and Pb uptake by pakchoi. Microaggregates exhibited predominant accumulation of Cd and Pb were in organic matter-bound and residual states, whereas in macroaggregates (> 250 μm), these metals were primarily associated with Fe-Mn oxide-bound and residual states. Furthermore, inoculation with these strains altered the bacterial community composition, specifically increasing the relative abundance of Proteobacteria, Sphingomonadaceae, and Micrococcales in microaggregates, which further contributed to the reduction of Cd and Pb uptake by pakchoi. These findings provide both valuable bacterial resources and a soild theoretical foundation for developing safe vegetable production strategies in heavy metal-contaminated fields.